2006
DOI: 10.1001/archopht.124.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Visual and Hearing Impairment and Risk of Mortality

Abstract: To determine the association between reported concurrent visual and hearing impairment and risk of mortality. Design, Setting, and Participants: Annual crosssectional multistage area probability surveys of the US civilian noninstitutionalized population living at addressed dwellings were conducted by the National Center for Health Statistics, Hyattsville, Md. Mortality linkage with the National Death Index of participants from 1986 to 1994 was performed through 1997. Complete reported visual and hearing impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
61
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 45 publications
9
61
0
1
Order By: Relevance
“…Second, Lieberman et al reported a 35 percent prevalence rate in an institutionalized population [17], consistent with other studies showing higher single sensory impairment rates in this unique group of older adults. Third, Lam et al found a low DSI prevalence rate of 1.3 percent by including a wider community-based age range that included adults as young as 18 [12], which probably skewed the data.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Second, Lieberman et al reported a 35 percent prevalence rate in an institutionalized population [17], consistent with other studies showing higher single sensory impairment rates in this unique group of older adults. Third, Lam et al found a low DSI prevalence rate of 1.3 percent by including a wider community-based age range that included adults as young as 18 [12], which probably skewed the data.…”
Section: Introductionmentioning
confidence: 98%
“…One study reported that hearing impairment did not increase depressive symptoms in participants with vision impairment [10]. In comparison with a single sensory impairment, DSI is associated with lower healthrelated quality of life [11] and increased risk of mortality [12]. Interestingly, one report found that individuals with vision impairment also may have poorer hearing sensitivity than individuals without vision impairment, suggesting an underlying biological contribution to impairments with both senses [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] İlginç olarak, görme azalmasına eşlik eden duyma azalması varlığında mortalite riskinin daha da arttığı ortaya konulmuş, yapılan bir çalışmada ırk ve cinsiyetten bağımsız olarak birebir ilişkinin varlığı bildirilmiştir. 6 Benzer olarak Blue Mountain Eye Çalışması bünyesindeki 55 yaş üstü 2812 hastanın 10 senelik takip sonuçlarında da tüm diğer risk faktörlerü dışlandığında kombine görme ve duyma kaybının bağımsız olarak mortalite riskini arttırdığı ve bu riskin tek başına görme veya tek başına duyma kaybına oranla daha fazla olduğu gösterilmiştir. 7 Gerçekten de görme keskinliğinde azalma, artmış mortalite riskini öngörebilir mi?…”
unclassified